PENGENDALIAN RISIKO COVID-19 PADA TENAGA KESEHATAN DI PUSKESMAS X KABUPATEN TEGAL - Nasikhati Arikoh (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
From the first case COVID-19 in Indonesia until July 2022, there were 6.088.460 cases. The study aims to determine how to control the risk of COVID-19 in health workers, especially in community health centers. The method used is descriptive qualitative. The instruments used are observation sheets, interview, and documentation. The results show that there are appropriate and not appropriate COVID-19 risk control related to hand hygiene, personal protective equipment, administrative, education and training.